Desenvolvimento de uma placa de acionamento para aplicação em robôs da categoria ieee very small size através de bluetooth - Morais Júnior, Hildo Soares de (Universidade Federal Rural do Semi-Árido, 2018)
The Very Small Size is one of the major categories of existing robot soccer. Within this category there are several limitations as to the dimensions of electronic circuits. In this way, this work aims at the construction of an electronic circuit controlled by bluetooth that can be embedded in the architecture of the robot. Since bluetooth data reception tests must be done on each robot, this project also provides a means to test the communication in each robot through an application. Experiments were performed to measure the response to commands made from the application, observing the output at the terminals of each motor. The results show the signals obtained for each position reference command of the robot, as well as the RMS voltage values received by the motors.
Monografia
Keywords: Robótica; Futebol de robô; Eletrônica; Comunicação bluetooth; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA